RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI PEMBAYARAN SISWA BERBASIS WEB DI SMK KESEHATAN MANDALA BHAKTI SURAKARTA - Ni’mal ‘Abdu, Aghni Rizqi; Purwanto, Eko; Permatasari, Hanifah (Universitas PGRI Semarang, 2022)
Mandala Bhakti Health Vocational School Surakarta is a vocational school that focuses on the health sector and has two majors, namely nursing and pharmacy. The use of computers at the Mandala Bhakti Health Vocational School in Surakarta has begun to be applied to help work in the field of school administration, especially the student payment administration section which serves all student payments including medical tests, tuition fees, practicum, competency tests, re-registration, and registration.However, the administrative process for student payments still takes quite a long time because students must first write a payment slip and wait for a payment receipt from the treasurer which is written manually and the recording process must be done twice, namely per day and class. In addition, the passbooks and receipts that are used by students to see the payments that have been made, are mostly lost and damaged, making students not know what bills to pay. Therefore, it is necessary to have a Student Payment Administration Information System that can speed up the payment process, simplify the reporting process, and grant access rights for students to view payment history and bill payments.This Student Payment Administration Information System was created based on a website using visual studio code software (text editor), MySQL database management system (DBMS), Xampp, and the PHP programming language. Methods of data collection are done using interviews, observation, and literature study. While in its construction, the author uses the RAD (Rapid Application Development) development method which consists of requirements analysis, modeling analysis, modeling design, and construction.Testing the student payment administration information system uses black box testing which shows that the system is functioning properly without any errors. User testing was carried out using a questionnaire which showed the results that for the admin, treasurer, and principal access rights questionnaire the highest score was the 'agree' option with a percentage of 60%, while for the student access rights questionnaire, the highest score was the 'agree' option. with a percentage of 55%. This shows that the student payment administration information system is following the needs of its users